Nyadran Rituals and Economic Resilience in Moderate Muslim Communities of Kendal - Tantowi, Ahmad; Ahmad, Nehru Millat (Universitas Islam Kadiri, 2025)
This article examines how Nyadran rituals underpin economic resilience in moderate Muslim communities in Gebangan Village, Pageruyung District, Kendal, Central Java. The study conceptualizes Nyadran as a religious and socio-economic institution that generates bonding and bridging social capital, sustains norms of mutual help, and supports income-smoothing strategies. A convergent mixed-methods design combines a household and microenterprise survey with in-depth interviews with religious leaders and Nyadran organizers, alongside participant observation of key ritual stages. Quantitative data are analyzed using multivariate regression to estimate the association between Nyadran participation, indicators of religious moderation, and a composite household economic resilience index. Qualitative findings elucidate mechanisms such as shared provisioning, reciprocal gifting, and informal safety nets that reduce vulnerability to shocks and shorten recovery time. Results show that higher involvement in Nyadran is positively associated with economic resilience, mediated by strengthened trust, civic engagement, and inclusive interpretations of Islam. The article contributes to international debates on religious moderation and resilience by demonstrating how a localized Islamic ritual operates as everyday civic infrastructure that supports community-based economic stability in peripheral Indonesian settings.